ANALISIS PENYEDIAAN FASILITAS UMUM OLEH PEMKOT SURABAYA - Melinawati, Minarsih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is the performance of Surabaya municipal in providing flats on Jl. Urip Sumoharjo no. 42. The descriptive study is type of research which is applied in this research. The qualitative descriptive isapplied in this research as the data analysis technique in this research in order to find out the characteristic ofrent rates, facility, location and environment of the flats on Jl. Urip Sumoharjo no 42 and then it is analyzed and it gives a conclusions based on the result of the analysis. This research responder is dweller of flats UripSumoharjo. The result of this this research indicates that the rent rate, facility, location and environment of theflats on Jl. Urip Sumoharjo no. 42 is already in appropriate with the prevailing rules in the Surabaya municipal.The aspect of rent rate of the flats indicates that the tenant of the flats do not satisfy with the rent rate which is asmuch as Rp 104,000 per month. The aspect of facilities of the flats indicate that the tenants of the flats feel quitesatisfied with the existing facilities of the flats of Jl. Urip Sumoharjo. The aspect of location indicates that thetenants of the flats feel satisfied with the location which is located in the center of Surabaya. The aspect ofenvironment indicate that the tenants of flats feel very satisfied with the environment of the flats UripSumoharjo. Â Keywords:Â  public facility providing, flats, Municipal of Surabaya